Statin drugs mitigate cellular inflammatory response after ST elevation myocardial infarction, but do not affect in-hospital mortality - Leili Pourafkari (Journal of Cardiovascular and Thoracic Research, 2016)
Introduction: The objective was to examine the role of statins in modulating post-STEMI inflammation and related mortality. Methods: A total of 404 patients with STEMI were reviewed. Demographics, comorbidities, laboratory values, and outcomes were collected. The patients were grouped as STATIN and NOSTAT based on the use of statin drugs at the time of admission. Ninety-seven patients were receiving statin drugs. Results: The patients in the STATIN group were more likely to be hypertensive (53.6%), diabetic (37.1%) and to have previous coronary revascularization (9.3%). Following propensity matching of 89 patients in STATIN group to an equal number of patients in NOSTAT controls had lower neutrophil count 7.8 (6.8-8.4) compared to those in the NOSTAT group 9.1 (7.9-10.1). Although there was no difference in-hospital mortality between the two groups, the incidence of pump failure was lower in the STATIN group (5.6% vs. 15.7%; P<0.01). Conclusion: Statin treatment prior to STEMI mitigates the cellular inflammatory response after the myocardial infarction, as evidenced by lower leukocyte and neutrophil cell counts in the STATIN group.